LC-MS/QTOF identification of phytochemicals and the effects of solvents on phenolic constituents and antioxidant activity of baobab (Adansonia digitata) fruit pulp. (30th March 2019) - Ismail, Balarabe B.; Pu, Yunfeng; Guo, Mingming; Ma, Xiaobin; Liu, Donghong
Highlights: 46 phytochemicals belonging to 7 sub-classes were detected in baobab fruit pulp. Proanthocyanidins, phenolic acids, flavonols, and saponins were the most common compounds. Phenolic acids and flavonoids contents varied significantly in different solvent extracts. Baobab fruit pulp contains 1–6 times more TFC than TPC. 80% acetone was determined as the best solvent for TPC, TFC and antioxidant activity. Abstract: Baobab fruit ( Adansonia digitata ) pulp has received a growing attention globally for its numerous nutritional and medicinal values. However, only limited information is available about its phytochemical composition. The purpose of this study was to identify the phytochemicals in baobab fruit pulp using LC-MS/QTOF and evaluate the effects of solvents on phenolic compounds content and antioxidant activity. The LC-MS analysis led to the identification of 46 compounds, based on standards and comparison with literature reports. Proanthocyanidins, phenolic acids, flavonols, and saponins were the most common compounds. The best solvent for Total Phenolic Compounds Content (TPCC), TPC, TFC and antioxidant activity was also defined: 80% acetone was the best for TPCC, TFC and FRAP, 30% acetone for TPC and 50% methanol for DPPH. Considering all the results, 80% acetone was determined as the best solvent for sample extraction. A high correlation was observed between phenolic compounds content and antioxidant activity.